Conceptual model for the integration of personal attribute skills in electrical technology education curriculum - Dahiru Sale Mohammed; Sarimah Ismail (Institute of Advanced Engineering and Science, 2019)
The current curriculum of Electrical Technology Education (ETE) of Nigerian Universities has been criticized for not meeting the desired challenges. The personal attribute skills were found are not integrated in the curriculum. Hence, a study was conducted to determine the types of personal attribute skills, their respective indicators and to develop a conceptual model for the integration of personal attribute skills for ETE curriculum. Mixed methods exploratory research design was employed for the study. 10 industry technical managers were interviewed and the interview data were analyzed using coding process of open coding, axial coding and selective coding. The interview data were used to develop a structured questionnaire that validated by 4 experts. Alpha value for pilot test was 0.89. Sample of the survey were 646 including 528 ETE graduates, 22 ETE lecturers and 96 industry technical managers. Stepwise Linear Regression and Confirmatory Factor Analysis were used to analyze the survey. The study developed a conceptual model for the integration of personal attribute skills that consists of two major skills: attitude skills and trait skills. This study recommended the implementation of the conceptual model for the integration of employability skills in ETE curriculum.